Vincere [videorecording (DVD)] - Bellocchio, Marco, 1939-; Bellocchio, Marco, 1939-; Mezzogiorno, Giovanna, 1974-; Timi, Filippo, 1974-; Alesi, Fausto Russo; Cescon, Michela; Bellocchio, Pier Giorgio (IFC Films : MPI Media Group [distributor], 2010)
About fascist dictator Benito Mussolini and the woman he loved. Ida Dalser was scorned, denounced, and then written out of history. Mussolini's rise to power and Dalser's descent into an insane asylum are tragic counterpoints in a doomed romance. Dalser may have been written off at the time, but Bellocchio and Mezzogiorno allow her a final, unexpected triumph in this cinematic masterwork.